2016
DOI: 10.1111/epi.13569
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility trial of an Internet‐delivered and transdiagnostic cognitive behavioral therapy treatment program for anxiety, depression, and disability among adults with epilepsy

Abstract: The findings of the current study support the feasibility and potential of transdiagnostic Internet-delivered treatments for adults with epilepsy. Further large-scale controlled trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…14 This is an important area for future research to address, especially given that co-occurring anxiety and depression appear to be associated with poorer outcomes in PWE, 6 and emerging treatments that aim to treat both comorbidities simultaneously. 39 The literature examining psychiatric comorbidity in PWE has long accepted that epilepsy has a strong relationship with depression, and that PWE are at significantly increased risk of depression compared to the general population. However, anxiety has been relatively neglected.…”
Section: Discussionmentioning
confidence: 99%
“…14 This is an important area for future research to address, especially given that co-occurring anxiety and depression appear to be associated with poorer outcomes in PWE, 6 and emerging treatments that aim to treat both comorbidities simultaneously. 39 The literature examining psychiatric comorbidity in PWE has long accepted that epilepsy has a strong relationship with depression, and that PWE are at significantly increased risk of depression compared to the general population. However, anxiety has been relatively neglected.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to recruit patients without geographical barriers also presents opportunities for testing psychotherapy for people with conditions and problems (e.g., spinal cord injury, epilepsy) that can be highly disabling while also having a relatively low prevalence, making them very difficult to study feasibly in face‐to‐face trials.…”
Section: Innovationmentioning
confidence: 99%
“…This intervention was delivered by trained facilitators via telephone or a Web‐based platform and included regular guided discussions. In another single‐arm study, reductions in depressive symptoms and several secondary outcomes were observed in a sample of 27 PwE who used a clinician‐supported Internet intervention . However, this study did not include a control group, and both studies included clinician‐support.…”
Section: Introductionmentioning
confidence: 99%